2022
DOI: 10.3390/ijms23063162
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response in Endothelial Cells to Catecholamine Stimulation Associated with Increased Vascular Permeability

Abstract: Disruption to endothelial cell homeostasis results in an extensive variety of human pathologies that are particularly relevant to major trauma. Circulating catecholamines, such as adrenaline and noradrenaline, activate endothelial adrenergic receptors triggering a potent response in endothelial function. The regulation of the endothelial cell metabolism is distinct and profoundly important to endothelium homeostasis. However, a precise catalogue of the metabolic alterations caused by sustained high catecholami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In healthy vessels, mental stress causes the release of norepinephrine which binds to ⍺1 receptors, stimulates smooth muscles, and results in vasoconstriction (Froese et al., 2020; Harris et al., 2000). On the other hand, mental stress also causes a rise in circulating epinephrine, leading to β2‐mediated vasodilation by increasing nitric oxide bioavailability, which is responsible for endothelium‐dependent vasodilation (Carter et al., 2005; Conti et al., 2013; García De Lomana et al., 2022; Joyner & Casey, 2009). The vascular endothelium has an important role in the control of vascular tone (Furchgott & Zawadzki, 1980; Sandoo et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy vessels, mental stress causes the release of norepinephrine which binds to ⍺1 receptors, stimulates smooth muscles, and results in vasoconstriction (Froese et al., 2020; Harris et al., 2000). On the other hand, mental stress also causes a rise in circulating epinephrine, leading to β2‐mediated vasodilation by increasing nitric oxide bioavailability, which is responsible for endothelium‐dependent vasodilation (Carter et al., 2005; Conti et al., 2013; García De Lomana et al., 2022; Joyner & Casey, 2009). The vascular endothelium has an important role in the control of vascular tone (Furchgott & Zawadzki, 1980; Sandoo et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…49 Furthermore, in vitro studies showed that high levels of catecholamine neurotransmitters trigger endothelial adrenergic receptors, leading to endothelial permeability and glycocalyx loss in endothelial cells. 177 Combined, these findings suggest also a contribution of increased sympathetic nerve activity to endothelial dysfunction in CKD.…”
Section: Sympathetic Nerve Activitymentioning
confidence: 94%
“…Certain metabolites have been found to exhibit a dose-response relationship with the adrenaline-noradrenaline equimolar treatment. 12 These 46 metabolites align with the glutathione-ascorbate cycle and nitric oxide biosynthesis pathway. Upon catecholamine stimulation, an increase in glucose consumption and aerobic respiration was observed in endothelial cells, which supports how catecholamine stimulation of endothelial cells can cause increased oxidative stress and nitric oxide metabolism, and is associated with increased vascular permeability.…”
Section: Letter To the Editor 125mentioning
confidence: 96%